Peran Kepala Desa dalam Meningkatkan Pembangunan Di Desa Kedungrejo Kecamatan Waru Kabupaten Sidoarjo - Safira Aulia Salma; Virania Azzahra Putri; Annisa Firdausi Fikri; Ertien Rining Nawangsari (Jurnal Syntax Transformation, 2021)
Kedungrejo,Waru,Sidoarjo is a village between Sidoarjo and Surabaya city. Kedungrejo is a village with the third-highest trade sector development in the Waru sub-district. With the potential have to support from the village government, especially the village head, so the development of Kedungrejo village can be better. The village have close relationship with the community so that the leadership role of the village head has a very strategic role in increasing the success of village development. This study aims to describe the leadership role of the village head in development the obstacles in village development.This study uses a descriptive qualitative research method leadership theory from Tjokroamidjojo leader as Motivator, Facilitator, and Mobilizer. Data collection techniques using interviews, observation, and documentation.Data analysis used an interactive model proposed by Miles & Huberman(2019) with Observation Persistence and Triangulation Techniques in testing the validity of the data. The results of the research analysis show that the role of the village head is good improving development in the village of Kedungrejo, the village head has carried out his role as a motivator, facilitator, and mobilizer following his duties, authorities, and functions to improving village development, although there are still some obstacles but can be overcome properly.